2018
DOI: 10.3390/ijerph15091978
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Non-Medical Prescription Drug Misuse Among a Treatment-Seeking Population: A Comparison with Illicit Drug Users

Abstract: Prescription drugs (PD) undoubtedly help people with various physical or psychiatric ailments. Nevertheless, they are often diverted and misused (use without prescription or for purposes/in ways not intended by the prescriber). This study compared the sociodemographic and clinical correlates of those who misused PDs, used illegal drugs and co-ingested both, to identify those who were at a high risk of misusing these drugs. Retrospective analysis of the treatment outcome monitoring (TOM) data for the period of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…This is especially important where illicit substances are used alongside OTC and/or POMs because this may be associated with a lower quality of life and greater mental health issues. 43 It is, therefore, essential to be able to offer timely and effective interventions to reduce the risk of using other substances, experiencing more severe functional problems and riskier drug-related behaviours. 44 Additionally, substitute treatment used in SMS may also be used inappropriately and people who access SMS are more likely to experience comorbid mental health conditions, be prescribed psychotropic medication and for unlicensed indications.…”
Section: Open Accessmentioning
confidence: 99%
“…This is especially important where illicit substances are used alongside OTC and/or POMs because this may be associated with a lower quality of life and greater mental health issues. 43 It is, therefore, essential to be able to offer timely and effective interventions to reduce the risk of using other substances, experiencing more severe functional problems and riskier drug-related behaviours. 44 Additionally, substitute treatment used in SMS may also be used inappropriately and people who access SMS are more likely to experience comorbid mental health conditions, be prescribed psychotropic medication and for unlicensed indications.…”
Section: Open Accessmentioning
confidence: 99%
“…40 The majority of these buprenorphine abusers were male (90%) with a mean age of 39.2 (SD 8.0) years; 52.5% were currently employed and 98% had at least 34 Those with primary and secondary education qualifications had higher odds (2.1 and 2.9 times, respectively) of misusing both prescriptions and illicit drugs than those with tertiary qualification and those working in managerial or professional roles had higher odds (4.4 and 7.4 times, respectively) of misusing prescription medicines only than those who were unemployed. 41 Due to the paucity of data on the prevalence of prescription medicine misuse in Singapore, we conducted 2 online internet surveys in 2015 42 and 2016. The aim of the studies was to determine: (i) whether survey respondents had heard of different prescription medicines; (ii) the prevalence of prescription medicine misuse in Singapore; and (iii) the demographic characteristics of those reporting misuse.…”
Section: Prescription Medicine Misuse In Singaporementioning
confidence: 99%
“…In another paper evaluating prescription medicine misuse among 2273 individuals who were seeking treatment for substance misuse in Singapore, 41 295 misused prescription medicines only, 811 used illicit drugs, and 263 misused a mixture of both prescription and illicit drugs; 904 were excluded from the study as they reported using alcohol only. It was found that those who were misusing prescription medicines were predominantly male (243, 82.4%) with a mean age of 41.2 (SD 11.4) years; 63.1% among this group ( n = 186) reported misusing benzodiazepines as their main drug and 18.6% ( n = 5) used codeine.…”
Section: Prescription Medicine Misuse In Singaporementioning
confidence: 99%
“…61.6% (n=162) used heroin as their main drug, 14.1% (n=37) misused benzodiazepines, and 11.8% (n=31) used amphetamines. It was found that educational level and occupational status were associated with different types of misuse [34]. Those with primary and secondary education qualifications had higher odds (2.1 and 2.9 times, respectively) of misusing both prescriptions and illicit drugs than those with tertiary qualification and those working in managerial or professional roles had higher odds (4.4 and 7.4 times, respectively) of misusing prescription medicines only than those who were unemployed [34].…”
Section: Prescription Medicine Misuse In Singaporementioning
confidence: 99%
“…In another paper evaluating prescription medicine misuse among 2273 individuals who were seeking treatment for substances misuse in Singapore [34]. 295 misused prescription medicines only, 811 used illicit drugs, and 263 misused a mixture of both prescription and illicit drugs.…”
Section: Prescription Medicine Misuse In Singaporementioning
confidence: 99%